2019
DOI: 10.3390/ijerph16010122
|View full text |Cite
|
Sign up to set email alerts
|

A Toxicogenomic Approach Reveals a Novel Gene Regulatory Network Active in In Vitro and In Vivo Models of Thyroid Carcinogenesis

Abstract: Epidemiological and experimental studies emphasize the link between environmental chemicals exposure and thyroid cancer. However, this association is strongly debated and the mechanisms of action of environmental thyroid carcinogens still need to be identified. The analysis of in vitro transcriptomic data developed to investigate the effects of chlorpyrifos on immortalized thyrocytes highlighted the impaired expression of genes involved in endodermal carcinogenesis. This endodermal carcinogenic gene-network (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In our models, this event is driven by ZFP36L2 inactivation in association with the reduced expression of thyroid-specific transcripts. This last is a hallmark of the transformation of thyrocytes [33]. Finally, apoptosis is an early and pivotal step in thyroid carcinogenesis, and ZFP36L2 inactivation results in its increase.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In our models, this event is driven by ZFP36L2 inactivation in association with the reduced expression of thyroid-specific transcripts. This last is a hallmark of the transformation of thyrocytes [33]. Finally, apoptosis is an early and pivotal step in thyroid carcinogenesis, and ZFP36L2 inactivation results in its increase.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous work, we observed that levels of the mRNA of ZFP36L2, a protein that can promote RNA degradation [50], were increased during thyroid development [32] and reduced during hypothyroidism promoted by environmental stressors [34], as well as during thyroid carcinogenesis [33,41]. Its role in thyroid development and function has not yet been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several risk factors that are closely associated with TC occurrence and development, including genetic factors, age, sex, environmental exposure and epigenetic alterations. Even though there have been improvements in the diagnosis and surgical treatment of TC, the disadvantages associated with treatment strategies should not be ignored ( 4 , 5 ). Furthermore, TC demonstrates an increasing morbidity year on year, along with high rate of recurrence and a younger age at diagnosis, indicating a requirement for additional research on TC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%